Mia the bridesmaid fairy - Meadows, Daisy (New York : Scholastic Inc., 2010)
Rachel and Kirsty try to help Mia track down the three magic charms that Jack Frost took.
2.
6-9.
Accelerated Reader AR
Keywords: Frost, Jack (Fictitious character) -- Juvenile fiction; Fairies -- Juvenile fiction; Magic -- Juvenile fiction; Weddings -- Juvenile fiction; Frost, Jack (Fictitious character) -- Fiction; Fairies -- Fiction; Magic -- Fiction; Weddings -- Fiction